Evaluation Instrument Development for Scientific Writing Instruction with A Constructivism Approach - Supriyadi, Supriyadi (Technium Social Sciences Journal, 2021)
This study was conducted to develop evaluation instruments for scientific writing instruction with a constructivism approach. The development of evaluation instruments is important to provide valid and reliable measurement to measure the success rate of scientific writing instruction with a constructivism approach. In order to achieve these objectives, the combined models of development, i.e. 4D and RDR were used. The implementation of the development consisted of four stages, namely the preliminary study, define, design, and product development. The research data were in the form of quantitative and qualitative data and the data sources were the students, lecturers, practitioners, and experts in relevant fields of study. Data analysis technique was the domain technique and t test statistical technique for related samples. Based on the results, the obtained development product in the form of the evaluation of the instruction of writing scientific papers were valid and reliable. The development product consisted of four types of evaluation devices, the assessment rubrics, portfolios, observation sheets, and learning journal. Based on the results of the four development products, the effectiveness test was valid and reliable so that it can be used to conduct evaluation of learning to write scientific papers with constructivism approach, both for the evaluation of the process and the evaluation of the learning outcomes.